PTFI Big Gossan Mine - Ventilation Design to Support the New Stope Sequence Strategy - Diaz, Z; Sulistiyo, E; Sani, R (PERHAPI, 2018)
Big Gossan (BG) mine is an open stope mine operated by PT Freeport Indonesia(PTFI). This mine started its development in 2006. Currently, the mine consists of 9 active levels, each level is designed with about 1 km footwall drift East-West. The production initiated in 2009, but the mine was temporarily shut down due to a company decision. Lately the mine has been re-activated since 2017 and will be pushed into its peak production in 2019, with 7000 tpd production rate. In order to meet with the production goal, 5 levels consisting of 34 at least production stopes are required on a yearly basis. The other strategy to meet the production goal is an improvement of stopes sequencing. Big Gossan Mine is ventilated by two parallel 1600kW exhaust Mixed-Flow fans.This paper presents the ventilation plan and design to support the improved stope sequence until peak production, include the analysis of ventilation design criteria, ventilation network modeling, infrastructure required, possibility of main fans upgrade and other ventilation open stope mine challenges.